1998
DOI: 10.1152/ajpheart.1998.274.2.h500
|View full text |Cite
|
Sign up to set email alerts
|

Total arterial compliance estimated by stroke volume-to-aortic pulse pressure ratio in humans

Abstract: On the basis of the windkessel model, the stroke volume-to-aortic pulse pressure ratio (SV/PP) has been proposed as an estimate of total arterial compliance, but recent studies have questioned this approximation. Aortic pressure was obtained at rest in 31 adults undergoing cardiac catheterization (47 ± 14 yr): controls ( n = 7), patients with dilated cardiomyopathy ( n = 10), and patients with other cardiac diseases ( n = 14). We calculated PP, mean aortic pressure (MAoP), heart period ( T), SV (thermodilution… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
273
2
5

Year Published

1999
1999
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 316 publications
(288 citation statements)
references
References 29 publications
8
273
2
5
Order By: Relevance
“…6 Similarly, mean values here for AM correlate with those reported by O'Rourke et al 21 but not those reported by Liang et al 16 in similar patients. Values for SVPP observed in this study are higher than those reported by both Chemla et al and de Simone et al 12,22 This is presumably related to the method of measurement of SV. This lack of uniformity among measures of TAC between studies may be hard to interpret, however, most of these studies show the same differences within groups with and without risk.…”
Section: Heterogeneity Of Measures Of Total Arterial Compliancecontrasting
confidence: 77%
See 2 more Smart Citations
“…6 Similarly, mean values here for AM correlate with those reported by O'Rourke et al 21 but not those reported by Liang et al 16 in similar patients. Values for SVPP observed in this study are higher than those reported by both Chemla et al and de Simone et al 12,22 This is presumably related to the method of measurement of SV. This lack of uniformity among measures of TAC between studies may be hard to interpret, however, most of these studies show the same differences within groups with and without risk.…”
Section: Heterogeneity Of Measures Of Total Arterial Compliancecontrasting
confidence: 77%
“…It is not generally accepted as a calculation or estimation of C but rather an index of normal/abnormal compliance. 12 SV (LVOT CSA * LVOT VTI) and CO (SV * HR) were determined according to the ASE standard 13 and total vascular resistance was determined as mean arterial pressure MAP/CO (where LVOT ¼ left ventricular outflow tract; VTI ¼ velocity time integral; HR ¼ heart rate; MAP ¼ mean arterial pressure; CO ¼ cardiac output; SV ¼ stroke volume).…”
Section: Applanation Tonometrymentioning
confidence: 99%
See 1 more Smart Citation
“…The reproducibility of all the measurements has been reported to be satisfactory. 12,15 With respect to sensitivity to disease processes Lehmann has discussed PWV and stated: 'The presence of advanced atherosclerosis has been correlated with the degree of aortic stiffening in animal studies, but not so far in human beings'. 16 However this is not true for measures of central aortic compliance 17,18 or magnetic resonance imaging methods.…”
Section: Discussionmentioning
confidence: 99%
“…This is termed SV/PP and has a good correlation between central compliance calculated using the area method. 12 …”
Section: Central Aortic Compliancementioning
confidence: 99%